Quality of pomegranate fruits as influenced by pre harvest bagging under hot arid climate (Indian Journal of Arid Horticulture, 2021)
An experiment was conducted to study the effect of different bagging material on fruit quality and cracking in pomegranate which is severe problem under hot arid climate of Rajasthan. Pomegranate fruits of cv. Bhagwa were covered with different bagging material i.e. white paper bags, brown paper bags, butter paper bags, perforated transparent polyethylene bags, muslin cloth bags, markin cloth bags, non woven fabric bags, shrink wrapping (cling film) and control without bagging. The fruits were covered in each treatment after two month of fruit set during September and data were recorded on different fruit physical and physico-chemical quality attributes. Among the treatments, perforated transparent poly bags were significantly reduced fruit cracking (11.12%) as against control (25.20%). Perforated transparent polyethylene bags also resulted in highest marketable yield (4.72 kg/plant) followed by butter paper bags (4.00 kg/plant) as compared to lowest in control (3.30 kg/plant). Improved bright red colour fruits was obtained in perforated transparent poly bags and shrink wrapping treatments, while in control fruits colour faded and turn light brown red due to sun scald and frost damage. The total soluble solids and TSS/acid ratio were significantly affected by fruit bagging material, while non significant differences were observed in ascorbic acid, total sugar, reducing sugars and acidity of fruits. The maximum maturity index was recorded in perforated transparent polyethylene bags (35.82) followed by butter paper bags (31.91) as compared to minimum observed in control (25.12). Thus, pre harvest fruit bagging of pomegranate not only improved marketable fruit yield and quality of fruits but also significantly reduced fruit cracking under hot arid climatic conditions.
Keywords: Fruit bagging; fruit cracking; maturity index and quality